2020
DOI: 10.1016/j.jaip.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children: An Epidemiology Study from China

Abstract: Practice Options from Beyond Our Pages focuses on identifying, critiquing, and placing into context research studies published in other journals that have the potential to change our clinical practices. It is written by Allergy-Immunology Fellows partnered with faculty members, and does not require an invitation for submission. This feature is coordinated by Editorial Board members

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The COVID-19 (coronavirus disease 2019) pandemic caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) has spread worldwide [ 1 ]. Although serious COVID-19 can be a fatal disease, asymptomatic or mild cases of SARS-CoV-2 infections have been found [ [2] , [3] , [4] , [5] ]. It has also been reported that individuals with asymptomatic COVID-19 and those before developing symptoms can be infectious [ 6 , 7 ], suggesting that those with subclinical infection can contribute to the spread of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 (coronavirus disease 2019) pandemic caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) has spread worldwide [ 1 ]. Although serious COVID-19 can be a fatal disease, asymptomatic or mild cases of SARS-CoV-2 infections have been found [ [2] , [3] , [4] , [5] ]. It has also been reported that individuals with asymptomatic COVID-19 and those before developing symptoms can be infectious [ 6 , 7 ], suggesting that those with subclinical infection can contribute to the spread of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Among the confirmed cases, only 0.93% are found to be in the age group <10 years [3,5]. Of the patients in the age group of <18 years, 4.4% were asymptomatic [4].…”
Section: Discussionmentioning
confidence: 94%
“…It is speculated that children are less sensitive to SARS-CoV-2 because the maturity and function (e.g., binding ability) of ACE2 in children may be lower than that in adults [3,7]. Moreover, as children are frequently exposed to respiratory viruses (many RNA viruses, e.g., RSV and influenza), it can increase serum antibody level and offer cross-protection [3,4,7,8]. de Rose et al from Italy proposed the possibility of cross-protective effect of various pediatric vaccines [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen cases were ‘critical’—quickly progressing to ARDSÂąshock, encephalopathy, myocardial injury, heart failure, coagulation dysfunction and acute kidney injury—seven of whom were less than 1 year of age. 11 The authors did not report the patient’s comorbidities.…”
Section: Discussionmentioning
confidence: 99%